Learning Analytics : Assisting Universities with Student Retention : Project Outcome : Institutional Analytics Case Studies. - West, Deborah (Office for Learning and Teaching, 2015)
Online learning platforms in conjunction with learning analytics software and student information systems can offer higher education providers with deeper, more meaningful and timely data with which to understand factors impacting student retention than has previously been possible. This provides opportunities for targeted interventions to address critical, time sensitive retention-related issues. This document presents case studies from a project that focused on the use of learning analytics to improve outcomes for students, particularly on retention and equity groups. The project included two national surveys at an institutional and academic level to gather data on key infrastructure, the use of data and its application to improve teaching, learning and support to retain students. Survey data was aligned with identified retention variables to develop a framework for critically reflecting on and providing guidance on how analytics can be used to retain students.